Atmospheric moisture pathways of East Africa and implications for water recycling at Mount Kilimanjaro. (15th January 2020) - Schumacher, Benjamin; Katurji, Marwan; Meyer, Hanna; Appelhans, Tim; Otte, Insa; Nauss, Thomas
Abstract: The Mt. Kilimanjaro ecosystem depends on atmospheric moisture transport and recycling of water, yet limited knowledge on the relation between advective moisture pathways and local water recycling is available. This study uses a regional atmospheric model to analyse moisture source and sink processes as well as precipitation recycling at Mt. Kilimanjaro. The results indicate that locally produced precipitation is deposited mainly in June and July while trans‐regional effects are weak. Results also revealed the importance of tropical storm systems for local convection in the Kilimanjaro region and the effect of the Indian Ocean Zonal Mode phases on East African moisture pathways. The analysis further revealed connections between the Madagascar tip jet and the Turkana jet with implications for regional moisture pathways that have not been described before. Abstract : The Mt. Kilimanjaro ecosystem depends on atmospheric moisture transport and recycling of water which is deposited through local and trans‐regional processes. Locally produced precipitation is mainly deposited in July and August. However, in the rainy seasons trans‐regional moisture inflow can be highly affected by tropical storm systems like "Hellen" (March 2014—see image). Additional analysis of the East African moisture flow revealed connections between the Madagascar tip jet and the Turkana jet with implications for regional moisture pathways that have not been described before.